Characterization of Stem Cells and Immune Cells in Preterm and Term Mother's Milk. (August 2019) - Li, Shujuan; Zhang, Lan; Zhou, Qi; Jiang, Siyuan; Yang, Yi; Cao, Yun
Background: Human milk is known to be rich in cellular components, including stem cells and immune cells. However, the dynamics of these cellular components at different lactation stages, and the differences between milk for preterm and term infants, are poorly understood. Research aim: To identify changes in the cellular components of human milk at different lactation stages, and to explore the associations of these changes with maternal and infant characteristics. Methods: Forty mothers of newborns of different gestational ages were enrolled. Colostrum, transitional, and mature milk samples were collected. Stem cell and immune cell molecule markers were detected using flow cytometry. Pluripotent genes (SOX2, NANOG, OCT4, and KLF4) were detected via quantitative real-time PCR. Results: Human milk contained some stem cells but more immune cells. The percentages of hemopoietic stem cells were significantly higher in mature milk than in colostrum, and the percentages of total immune cells were lower in mature milk than in colostrum. The percentages of hemopoietic stem cells in colostrum and transitional milk were influenced by gestational age. Some minor differences in the cell composition of human milk could be explained by maternal body mass index, the mode of delivery, and parity. Conclusion: Our results again confirmed that human milk contains stem cells. Additionally, the percentages of hemopoietic stem cells and major immune cells changed dynamically at different lactation stages and were associated with gestational age at delivery.